UPPER MANTLE STRUCTURE OF THE NORTHERN EURASIA FROM PEACEFUL NUCLEAR EXPLOSION DATA - Pavlenkova G.A.; Pavlenkova N.I. (My University, 2006)
Several long-range seismic profiles were carried out in Russia with Peaceful Nuclear Explosions (PNE). The data from 25 PNEs recorded along these profiles were used to compile a 3-D upper mantle velocity model for the central part of the Northern Eurasia. 2-D crust and upper mantle models were also constructed for all profiles using a common methodology for wavefield interpretation. Five basic boundaries were traced over the study area: N1 boundary (velocity level, V = 8.35 km/s; depth interval, D = 60-130 km), N2 (V = 8.4 km/s; D = 100-140 km), L (V = 8.5 km/s; D = 180-240 km) and H (V = 8.6 km/s; D = 300-330 km) and structural maps were compiled for each boundary. Together these boundaries describe a 3-D upper mantle model for northern Eurasia. A map characterised the velocity distribution in the uppermost mantle down to a depth of 60 km is also presented. Mostly horizontal inhomogeneity is observed in the uppermost mantle, and the velocities range from the average 8.0-8.1 km/s to 8.3-8.4 km/s in some blocks of the Siberian Craton. At a depth of 100-200 km, the local high velocity blocks disappear and only three large anomalies are observed: lower velocities in West Siberia and higher velocities in the East-European platform and in the central part of the Siberian Craton. In contrast, the depths to the H boundary are greater beneath the craton and lower beneath in the West Siberian Platform. A correlation between tectonics, geophysical fields and crustal structure is observed. In general, the old and cold cratons have higher velocities in the mantle than the young platforms with higher heat flows. Structural peculiarities of the upper mantle are difficult to describe in form of classical lithosphere-asthenosphere system. The asthenosphere cannot be traced from the seismic data; in contrary the lithosphere is suggested to be rheologically stratified. All the lithospheric boundaries are not simple discontinuities, they are heterogeneous (thin layering) zones which generate multiphase reflections. Many of them may be a result of fluids concentrated at some critical P-T conditions which produce rheologically weak zones. The most visible rheological variations are observed at depths of around 100 and 250 km. © 2006 Elsevier B.V. All rights reserved.
Keywords: NUCLEAR EXPLOSIONS; SEISMIC STUDIES; SIBERIA; UPPER MANTLE